Evaluation of the ability of STD laboratories to detect Chlamydia trachomatis in Guangdong province - Xiaolin QIN; Yang CHEN; Yaohua XUE; Qingqing XU; Jiangli OU; Qiaozhen XU; Xingzhong WU; Wentao CHEN; Xiaona YIN; Han ZHOU; Ziyan ZHANG; Dan LIU; et al. (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To evaluate the ability of sexually transmitted disease (STD) laboratories in different medical institutions to detect Chlamydia trachomatis in Guangdong province. Methods The samples of Chlamydia trachomatis were prepared and distributed to all participants, without specified detection methods. The test results, methods and reagents were reported through the EQA online reporting system of provincial STD laboratory. If the results agreed with the expected results, a score of 2 would be achieved. Otherwise, the score was zero. The test results from different medical institutions, the types of STD laboratories and testing methods were compared. Results A total of 694 laboratories, including 388 secondary and higher-level medical institutions, 82 maternal and child health institutions, 79 chronic disease prevention institutions, and 145 primary or other medical institutions, participated in the evaluation of the inter-laboratory ability. Of the 694 laboratories, 537 were standardized STD laboratories and 157 were general laboratories. The overall conformity rate was 96.11%, with a qualification rate of 98.70%. Notably, the conformity rate of laboratories in chronic disease prevention institutions was the highest (98.23%). The standardized STD laboratories achieved significantly higher scores (Z=4.25) and qualification rates (χ2=22.87) than non-standardized laboratories (both P<0.001). Additionally, the nucleic acid testing method yielded a significantly higher score than the immunochromatographic method (Z=3.72, P<0.001). Conclusions The ability to detect Chlamydia trachomatis is high in the STD laboratories in Guangdong province. As the institutions dedicated to the prevention and treatment of STDs, skin venereal disease prevention and control institutions show a higher conformity rate. Moreover, standardized STD laboratories demonstrate higher detection ability than the non-standardized STD laboratories. Therefore, strengthening the standardization of STD laboratories can effectively improve the detection ability. Meanwhile, the nucleic acid testing method is recommended for Chlamydia trachomatis in clinical practice.